2019
DOI: 10.3389/fphar.2018.01563
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With a Flavonoid-Rich Fraction of Bergamot Juice Improved Lipopolysaccharide-Induced Periodontitis in Rats

Abstract: Objective: In this study, we investigated the effects of a flavonoid-rich fraction of Bergamot juice (BJe) in rats subjected to experimental periodontitis induced by a single intragingival injection of lipopolysaccharides (LPS).Main Methods: Periodontitis was induced by a single intragingival injection of 1 μl LPS (10 μg/μl) derived from Salmonella typhimurium in sterile saline solution. The injection was made in the mesolateral side at the interdental papilla between the first and the second molar. Fourteen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…Flavonoids stand out as promising anti-oxidant agents that may prove to be beneficial for treatment of human diseases associated with chronic inflammation, including atherosclerosis. For instance, flavonoid-rich fraction of bergamot juice was shown to reduce lipopolysaccharides-induced inflammation in rats [98], and flavonoid-rich extract of orange juice was observed to reduce oxidative stress in an experimental model of inflammatory bowel disease [99]. These findings reflect the capacity of flavonoids to positively affect the oxidative stress and related inflammation.…”
Section: Other Potential Anti-oxidant Agentsmentioning
confidence: 97%
“…Flavonoids stand out as promising anti-oxidant agents that may prove to be beneficial for treatment of human diseases associated with chronic inflammation, including atherosclerosis. For instance, flavonoid-rich fraction of bergamot juice was shown to reduce lipopolysaccharides-induced inflammation in rats [98], and flavonoid-rich extract of orange juice was observed to reduce oxidative stress in an experimental model of inflammatory bowel disease [99]. These findings reflect the capacity of flavonoids to positively affect the oxidative stress and related inflammation.…”
Section: Other Potential Anti-oxidant Agentsmentioning
confidence: 97%
“…A decrease in the activity of superoxide dismutase (SOD)—an endogenous anti-oxidative enzyme—accompanies an increased tissue malondialdehyde (MDA) concentration during ischemia, potentially predisposing the intestinal mucosa to I/R damage. Several previous studies from our group have described the beneficial effects of natural antioxidant treatments in different pathologies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Unfortunately, firocoxib did not display any antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that BJ, along with its flavonoid-rich extract (BJe), possesses antioxidant [27,35] and anti-inflammatory [33,[36][37][38][39][40] activities. We further demonstrated the antimicrobial effect of BJe [41], as well as its anti-cancer properties, both in vitro [24,25,42] and in vivo [26,43].…”
Section: Discussionmentioning
confidence: 99%